2021
DOI: 10.1002/smll.202102689
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Frameworks for Ammonia‐Based Thermal Energy Storage

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/smll.202102689.Recently, the application of metal-organic frameworks (MOFs) in thermal energy storage has attracted increasing research interests. MOF-ammonia working pairs have been proposed for controlling/sensing the air quality, while no work has yet been reported on the immense potential of MOFs for thermal energy storage up till now. Herein, the feasibility of thermal energy storage using seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…An et al suggested MIL-101 as the most suitable MOF for high-pressure NH 3 adsorption and desorption due to its high specific surface area and large pore size. 29 Chemical equilibrium between a metal center and NH 3 could affect the structural stability of MOFs, and strong bonding between a metal center and an organic linker could be helpful to maintain the framework stability upon NH 3 adsorption-desorption cycles. Moreover, improvement of NH 3 adsorption-desorption rates in MOFs would allow efficient mass and heat transfer in AHPs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An et al suggested MIL-101 as the most suitable MOF for high-pressure NH 3 adsorption and desorption due to its high specific surface area and large pore size. 29 Chemical equilibrium between a metal center and NH 3 could affect the structural stability of MOFs, and strong bonding between a metal center and an organic linker could be helpful to maintain the framework stability upon NH 3 adsorption-desorption cycles. Moreover, improvement of NH 3 adsorption-desorption rates in MOFs would allow efficient mass and heat transfer in AHPs.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, only few articles have recently appeared to demonstrate MOFs as potential NH 3 adsorbents in AHPs (Table 1). [27][28][29] We begin to introduce the operating principle of AHPs for better understanding important requirements of MOFs under high-pressure NH 3 environment. AHPs provide heating or cooling from thermal energy, different from compression heat pumps operated by mechanical energy.…”
Section: High-pressure Nh 3 Adsorption (>5 Bar)mentioning
confidence: 99%
See 1 more Smart Citation
“… 26 Recent reports for high-pressure ammonia adsorption demonstrated that MIL-101 was evaluated as the most stable MOF with higher ammonia uptake than other MOFs (MOF-801, MOF-841, DUT-67, NU-1000, UiO-66, and MIL-100). 7 , 27 In addition, introducing heterogeneous metal components has shown synergistic effects in gas adsorption and catalysis. 28 33 Noble metals (Pt, Pd, Rh, Au, and Ag) have strong affinity for ammonia, 34 and silver nanoparticles could display increasing selectivity for ammonia sensing on carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…MIL-101 consists of μ 3 -oxo bridged chromium-trimers with terephthalic acid ligands, and it has a relatively large surface area with hierarchical pore structures and high structural stability against water, oxygen, organic solvents, and heat . Recent reports for high-pressure ammonia adsorption demonstrated that MIL-101 was evaluated as the most stable MOF with higher ammonia uptake than other MOFs (MOF-801, MOF-841, DUT-67, NU-1000, UiO-66, and MIL-100). , In addition, introducing heterogeneous metal components has shown synergistic effects in gas adsorption and catalysis. Noble metals (Pt, Pd, Rh, Au, and Ag) have strong affinity for ammonia, and silver nanoparticles could display increasing selectivity for ammonia sensing on carbon nanotubes . We anticipated that relatively low ammonia desorption energy and cost of Ag among the noble metals would be desirable for the heterogeneous component encapsulated in MIL-101.…”
Section: Introductionmentioning
confidence: 99%